Nephroprotective effects of enalapril after (177Lu)-DOTATATE therapy using serial renal scintigraphies in a murine model of radiation-induced nephropathy - Ilhan, Harun; Wang, Hao; Gildehaus, Franz J.; Wängler, Carmen; Herrler, Tanja; Todica, Andrei; Schlichtiger, Julia; Cumming, Paul; Bartenstein, Peter; Hacker, Marcus; Haug, Alexander R. (EJNMMI Research, 2016)
Radiation-induced nephropathy is still dose limiting in radionuclide therapy of neuroendocrine tumors. We investigated the nephroprotective potential of the angiotensine converting enzyme inhibiting drug enalpril after [177Lu]-DOTATATE therapy in a murine model of radiation-induced nephropathy by renal scintigraphy.